Ophelia : Shakespeare and gender in contemporary Spain - Ugalde, Sharon Keefe (Iberian and Latin American studies., 2020)
Ugalde's fascinating and well-documented study demonstrates how Spanish authors, dramatists and visual artists bring Shakespeare's desperate and suicidal heroine to life in new guises.